Strong Evidence for Gender Differences in Risk Taking - Charness, Gary; Gneezy, Uri (Journal of economic behavior & organization, 2012)
► We consider the results of 15 different studies on risk-taking in investment, each of which gathered data by gender. ► Each study used the same very simple and easy-to-comprehend mechanism for eliciting risk preferences. ► We find the extremely robust result that women are more risk averse than men. ► Most of the data were not collected in order to study gender differences, but rather to study other hypotheses regarding investment behavior, ameliorating the issue of publication bias with respect to gender results. Are men more willing to take financial risks than women? The answer to this question has immediate relevance for many economic issues. We assemble the data from 15 sets of experiments with one simple underlying investment game. Most of these experiments were not designed to investigate gender differences and were conducted by different researchers in different countries, with different instructions, durations, payments, subject pools, etc. The fact that all data come from the same basic investment game allows us to test the robustness of the findings. We find a very consistent result that women invest less, and thus appear to be more financially risk averse than men.